Obama's Cairo speech: reaching out to the Muslim world - Mohamed Ali, Haja Mohideen (2010)
President Barack Obama’s speech in Cairo in 2009 was primarily addressed to the Muslim world. He had sought to dispel the impression that the US is anti- Islam or anti- Muslim. No other US president had done this before. The Cairo speech is a classic example of persuasive discourse wherein the speaker praises Muslims for their past achievements and contributions while at the same time reminding them of certain shortcomings in Muslim- majority countries. He appealed for partnership between the US and the Muslim world for the common good of both. The present paper analyzes the language used in the speech text objectively. Quotes and lexical expressions from the speech are identified and analyzed to illustrate his conviction as well as his country’s “to seek a new beginning between the United States and Muslims around the world, one based on mutual interest and mutual respect, and one based upon the truth that America and Islam are not exclusive and need not be in competition.” The language used in the speech text is critically analyzed and described in the context of his attempt to reach out to the Muslim world to forge a new beginning. A critical interpretation will be made of the much heralded speech which had initially raised huge expectations among Muslims.